Evaluation Of PCR Method To Detect Fungal Aetiology In Microbial Keratitis. - Embong, Zunaina (2002)
Microbial keratitis is a serious ocular infection. It is often difficult to establish a microbial keratitis that is due to fungal infection. Inadequate therapy and delayed diagnosis of fungal keratitis leads to generally poor visual outcomes.